2018
DOI: 10.1080/00131911.2018.1424117
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualisation of school and teacher connectedness in adolescent research: a scoping review of literature

Abstract: The aim of this scoping review was to map and summarise research relating to school and teacher connectedness, in order to increase current understanding of the ways these terms have been conceptualised in adolescent research. Specifically, this scoping review focuses on the analysis of the actual definitions used and the ways in which school connectedness and teacher connectedness are operationalised in existing measures. Using the terms connectedness, teacher and school as keywords, we searched SCOPUS, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 88 publications
1
49
0
Order By: Relevance
“…Some studies have reported that the school is a context where adoptees suffer discrimination, racism, and bullying due to the stigma around adoption or to their different appearance in transracial adoptions (Baden, 2016; Raaska et al, 2012; Soares, Barbosa-Ducharne, Palacios, & Fonseca, 2017). This problem has been detected even in teachers (e.g., McGinnis, Livingston, Ryan, & Howard, 2009), which is shocking, given that social support from teachers has been identified as a fundamental factor for the achievement of positive outcomes and well-being (García-Moya, Bunn, Jiménez-Iglesias, Paniagua, & Brooks, 2018; Pössel et al, 2018).…”
Section: Social Support and Well-beingmentioning
confidence: 99%
“…Some studies have reported that the school is a context where adoptees suffer discrimination, racism, and bullying due to the stigma around adoption or to their different appearance in transracial adoptions (Baden, 2016; Raaska et al, 2012; Soares, Barbosa-Ducharne, Palacios, & Fonseca, 2017). This problem has been detected even in teachers (e.g., McGinnis, Livingston, Ryan, & Howard, 2009), which is shocking, given that social support from teachers has been identified as a fundamental factor for the achievement of positive outcomes and well-being (García-Moya, Bunn, Jiménez-Iglesias, Paniagua, & Brooks, 2018; Pössel et al, 2018).…”
Section: Social Support and Well-beingmentioning
confidence: 99%
“…They generally attribute scoping studies a comprehensive coverage. Our decision to conduct a scoping review was based on three reasons: First, as preliminary literature searches on the PET’s personality revealed that research in this field is diverse and the understanding of personality vague, a scoping review that typically does not try to find an answer to a specific question but summarizes what questions have been asked, seemed to be appropriate (McEvoy et al, 2015; García-Moya et al, 2018). Second, we were interested in the identification of certain characteristics or concepts related to personality and in mapping, reporting or discussing these with finally suggesting practical implications – according to Munn et al (2018) indications for a scoping review and therefore again supporting our decision.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, research with college and university students highlights how different forms of connectedness can affect, both positively and negatively, health and wellbeing outcomes (Conway et al, 2018; Hunt & Burns, 2017), with calls for better definitions of connectedness (Jorgenson et al, 2018). In a recent scoping review of literature, Garcia-Moya et al (2019) suggest that school connectedness is made up of two constructs: (a) The young person’s feelings towards the school as an institution and (b) The perception of specific relationships at school, particularly relationships with teachers. The same team is currently leading a study aimed at understanding the antecedents of teacher connectedness, to be able to maximise the public health potential of this relationship (The Teacher Connectedness Project, n.d.…”
Section: Connectedness and Healthmentioning
confidence: 99%
“…Internationally, connectedness research (e.g. Garcia-Moya et al, 2019;Rutter, 1982) has been consistent in highlighting the importance of social and relational factors to child and adolescent development, with impacts upon long-term achievements including academic attainment, social success and health outcomes (e.g. Resnick et al, 1997;Rutter, 1982;Sieving et al, 2014).…”
Section: Connectedness and Healthmentioning
confidence: 99%